Advancements In Monitoring water Quality Based On Various Sensing Methods: A Systematic Review - Siti Nadhirah Zainurin; Wan Zakiah Wan Ismail; Siti Nurul Iman Mahamud; Irneza Ismail; Khairul Nabilah Zainul Ariffin; Wan Maryam Wan Ahmad Kamil; Juliza Jamaludin (MDPI, 2024)
Indexed by WOS/Scopus/ERA